2011
DOI: 10.1007/s10900-011-9456-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors and Diabetes in Asian Indians Residing in Michigan

Abstract: Asian Indians are the largest Asian subgroup in the state of Michigan; however, data on the prevalence and correlates of cardiovascular disease for this group is limited. The sample consisted of 273 Asian Indians (AI) recruited through health fairs for surveys and blood tests throughout the state of Michigan. The prevalence of self-reported diabetes (20.1%) and elevated/abnormal glycated hemoglobin A1C levels (22.6%) exceeds the percentages of other ethnic groups reported in 2006-2008 Michigan Behavioral Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Therefore, the high prevalence of diabetes in one urban Indian city as reported in this study may be indicative of an even larger burden of disease in India yet to come. Furthermore, the diabetes prevalence in MASALA study participants was similar to what was found in a recently published study of Asian Indians in Michigan ( 27 ). However, additional national level data are needed to assess the prevalence of diabetes among Asian Indians living in the U.S.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the high prevalence of diabetes in one urban Indian city as reported in this study may be indicative of an even larger burden of disease in India yet to come. Furthermore, the diabetes prevalence in MASALA study participants was similar to what was found in a recently published study of Asian Indians in Michigan ( 27 ). However, additional national level data are needed to assess the prevalence of diabetes among Asian Indians living in the U.S.…”
Section: Discussionsupporting
confidence: 86%
“…Though most Chinese and South Asians in the study met the 5-a-day requirement, such results highlight potentially at-risk and overlooked groups. These results have significant implications to public health, as South Asians not only are the fastest growing population in the USA [42] but also have one of the highest rates of cardiovascular diseases [8,[43][44][45][46][47][48][49]. Such results are also consistent with previous literature [50] demonstrating that socioeconomic advantage was associated with better cardiovascular health among South Asians in other nations.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of BMI revealed that most of the women in this study were overweight and the men were obese. Asian Indians generally exhibit lower Body Mass Index and waist circumference and tend to accumulate intra-abdominal visceral fat when compared to Caucasians [12]. Studies report that BMI and waist circumference serve as parameters to estimate general or abdominal fat masses, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent research study focusing on Asian Indians from the state of Michigan found a high prevalence of self-reported type 2 diabetes (20.1%) and elevated/abnormal A1C levels (A1C ≥ 6.5%: 22.6%). It exceeded the percentages of other ethnic groups reported in the 2006–2008 Michigan Behavioral Risk Factor Survey (MBRFS) (8% for non-Hispanic whites, 13% for non-Hispanic blacks, 8.9% for Hispanic Latinos, and 15.6% for Native American/Alaskan natives) [12]. …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation